Dynamics of neutrino lumps in growing neutrino quintessence - Casas, Santiago; Pettorino, Valeria; Wetterich, Christof (Arxiv, 2016)
We investigate the formation and dissipation of large scale neutrino structures in cosmologies where the time evolution of dynamical dark energy is stopped by a growing neutrino mass. In models where the coupling between neutrinos and dark energy grows with the value of the scalar cosmon field, the evolution of neutrino lumps depends on the neutrino mass. For small masses the lumps form and dissolve periodically, leaving only a small backreaction of the neutrino structures on the cosmic evolution. This process heats the neutrinos to temperatures much above the photon temperature such that neutrinos acquire again an almost relativistic equation of state. The present equation of state of the combined cosmon-neutrino fluid is very close to -1. In contrast, for larger neutrino masses the lumps become stable. The highly concentrated neutrino structures entail a large backreaction similar to the case of a constant neutrino-cosmon coupling. A present average neutrino mass of around 0.5 eV seems so far compatible with observation. For masses lower than this value, neutrino induced gravitational potentials remain small, making the lumps difficult to detect.